Energi Baru Terbarukan (EBT) dan Pertumbuhan Ekonomi: Analisis Kausal terhadap Substitusi Energi, Lapangan Kerja Hijau, dan Kontribusi terhadap PDB: New Renewable Energy (NRE) and Economic Growth: A Causal Analysis of Energy Substitution, Green Employment, and Contribution to GDP - Khairunnisa, Nur; Supriyadi, Imam; Santoso, Budi (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The transition from fossil fuels to Renewable Energy (RE) represents a key strategy for promoting sustainable and low-carbon economic growth in Indonesia. This study examines the causal relationship between renewable energy development and economic growth through four main channels: the substitution effect from fossil fuels, the creation of green jobs, contributions to the energy sector’s Gross Domestic Product (GDP), and the impact on local economic growth in high-potential regions such as Nusa Tenggara, Sulawesi, and Kalimantan. The research employs a literature review with a descriptive qualitative approach, utilizing secondary data from national and international sources (Bappenas, ESDM, IEA, IRENA, ILO, World Bank).The findings indicate that increasing renewable energy capacity contributes to fiscal efficiency by reducing subsidies and fuel imports, while generating large-scale green employment opportunities that support local economic transformation. Moreover, renewable energy development produces a significant multiplier effect on regional economies, particularly in eastern Indonesia where energy potential is high but infrastructure remains limited. Overall, renewable energy plays a strategic role as a new engine of inclusive, competitive, and sustainable economic growth—provided that policy integration, green industrial development, technology transfer, and local workforce capacity strengthening are effectively implemented.